The influence of a hurdle target point on the kinematics of the handspring vault approach run during training - Dallas, G.; Theodorou, A. S. (Sports Biomechanics, 2020)
The aim of this study was to investigate if a visible target for the hurdle take-off would influence the onset of visual regulation and hurdle kinematics during the approach run. Ten elite male gymnasts (age 23.4 ± 4.9 years, height 1.68 ± 0.06 m, mass 63.3 ± 6.2 kg) performed six handspring vaults with a full approach run under two controlled conditions: (a) with a 5-cm white tape on the runway marking the last touchdown of the approach run and the commencement of the hurdle (tape condition—T) and (b) under the standard vaulting regulations (non-tape condition—NT). Spatiotemporal data of the approach run and the hurdle were collected by four stationary and one panning cameras (sampling rate 300 fps). Eight out of 10 gymnasts commenced regulation earlier under T than under NT. Under T condition, horizontal velocity (Vx to = 9.06 ± 0.41 m/s) and vertical velocity (V to = 9.35 ± 0.37 m/s) was significantly faster than under NT condition (Vx to = 8.85 ± 0.49 m/s; V to = 9.11 ± 0.47 m/s). Introducing a target for the hurdle facilitates an early onset of step regulation and significantly improves the kinematics of the hurdle.